2018
DOI: 10.3389/fpls.2018.00994
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Supply Affects Photosynthesis and Photoprotective Attributes During Drought-Induced Senescence in Quinoa

Abstract: Drought during senescence has become more common in Mediterranean climates in recent years. Chenopodium quinoa Willd has been identified as tolerant to poor soil conditions and drought. Previous observations have found that sufficient nitrogen (N) supply mitigates yield losses under terminal drought conditions. However, there is no understanding of the mechanisms behind this effect. We hypothesized that N up-regulates both photosynthetic and photoprotective elements during drought-induced senescence, alleviati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…Three lowland genotypes: Faro (latitude 34.47° and longitude 71.83°), UdeC9 (latitude 35.73° and longitude 72.53°) and BO78 (latitude 38,51° and longitude 71,4) from different geographical and climatic areas of Chile, but with similar morphological and phenological (senescing timing) characteristics, were used in this work. It has been reported that Faro increment its NUE value when developed at LN 27 , and display an enhanced level of photoprotective attributes when grown at LN compared with UdeC9 and BO78 42 . Faro seeds were obtained from Cooperative Las Nieves, whereas UdeC9 and BO78 seeds were provided for the National Seed Bank collection at Vicuña, Chile (INIA-Intihuasi).…”
Section: Methodsmentioning
confidence: 98%
“…Three lowland genotypes: Faro (latitude 34.47° and longitude 71.83°), UdeC9 (latitude 35.73° and longitude 72.53°) and BO78 (latitude 38,51° and longitude 71,4) from different geographical and climatic areas of Chile, but with similar morphological and phenological (senescing timing) characteristics, were used in this work. It has been reported that Faro increment its NUE value when developed at LN 27 , and display an enhanced level of photoprotective attributes when grown at LN compared with UdeC9 and BO78 42 . Faro seeds were obtained from Cooperative Las Nieves, whereas UdeC9 and BO78 seeds were provided for the National Seed Bank collection at Vicuña, Chile (INIA-Intihuasi).…”
Section: Methodsmentioning
confidence: 98%
“…Agreeing with BASCUÑÁN-GODOY et al (2018a), different varieties of quinoa can adapt to low contents of soil elements; however, some varieties express the best foliar development under conditions of nitrogen unavailability, since they find significant differences compared to Chilean varieties. These data agree with what was obtained, while BS presented the highest number of leaves structures during the entire production cycle compared to BJ and T.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…Additionally, citrulline and spermidine levels were 2-fold higher in Socaire than in Faro seeds. All these high nitrogen content compounds were related to drought and salinity tolerance in quinoa [27,28].…”
Section: Seed Composition Of Landracesmentioning
confidence: 95%
“…The major difference in these aboveground measured parameters between landraces was the capacity of Socaire plants to maintain qL values under LN conditions. Considering that photosynthesis is the principal process that explains qL values in Quinoa [28], this response could be the basis of the different amount of leaf protein between landraces under LN conditions. It is known that LN supply (and other stress conditions) induces production of secondary metabolites, triggering protein degradation and increasing photorespiration [31].…”
Section: Seed Composition Of Landracesmentioning
confidence: 99%